Palaeozoic evolution of the North Tianshan based on palaeomagnetic data – transition from Gondwana towards Pangaea - Kirscher, Uwe; Bachtadse, V.; Mikolaichuk, A.; Kröner, A.; Alexeiev, D. (Taylor & Francis Inc., 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis GroupWe present new palaeomagnetic data for Cambrian and Ordovician volcanic and sedimentary rocks from the Kyrgyz North Tianshan (NTS) and review available data from the southwestern Central Asian Orogenic Belt (CAOB) to elucidate the tectonic history and evolution of this region during the early Palaeozoic. We observed a coherent evolution of the NTS and the Kazakhstan continent (or Kazakhstania) with a constant northwards movement between the Cambrian and Devonian at ~5 cm/a. After the northwards movement ceased in the Devonian, the accreted terrane assemblage of Kazakhstania occupied a stable latitudinal position at ~30°N until the final amalgamation of Eurasia occurred in the late Carboniferous to early Permian. Amalgamation of the Tarim and Turan blocks caused a counterclockwise bending within the southwestern segment of the CAOB, which occurred in an inconsistent way by a brittle-like response of the upper crust with a large variety of rotational movement. We suggest an evolution of the Kyrgyz CAOB terranes by steady migration away from Gondwana and subsequent capture in a zone of global downwelling at ~30°N, where accretion and subsequent amalgamation of Eurasia occurred with the CAOB terranes in its centre.